Complying with Farm Labor Regulations: Correctly Counting Compensable Hours - Fritz M. Roka; Michael T. Bayer (EDIS, 2014)
United States law requires farm employers to keep accurate records of the number of daily compensable hours worked by their seasonal and migrant farm workers. The most prevalent and serious violations occur when agricultural employers do not correctly record the daily start and stop times for seasonal and migrant farm workers and so underreport the number of “compensable” hours for each worker. The purpose of this article is to discuss the concept of “compensable” hours in more detail and eliminate any confusion that might lead agricultural employers to make costly mistakes. This 4-page fact sheet was written by Fritz M. Roka and Michael T. Bayer, and published by the UF Department of Food and Resource Economics, February 2014.